1991
DOI: 10.1001/archsurg.1991.01410270082013
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Surgical Stress Impairment of Human Perioperative Natural Killer Cell Cytotoxicity

Abstract: Natural killer (NK) cells are an important defense against intravascular tumor dissemination. Tumor embolization can occur at surgery, so we tested whether surgical stress decreased perioperative NK cell cytotoxicity, and examined the underlying mechanism of suppression. Patients with solid tumors underwent NK cell cytotoxicity assay just before and 24 hours after surgery in a 3-hour chromium 51 release assay. The NK cell cytotoxicity was significantly decreased postoperatively. We considered that surgical NK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
1
4

Year Published

1993
1993
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(75 citation statements)
references
References 17 publications
3
67
1
4
Order By: Relevance
“…We also suggest that adrenergic suppression of NK activity may be a mechanism contributing to the adverse effects of surgery. Suppression of NK activity after surgery is well documented clinically (Pollock et al, 1991;Brittenden et al, 1996), was attributed by animal studies to adrenergic mechanisms (Ben-Eliyahu, 1998a), and was suggested by human and animal studies to promote metastasis (Zoller et al, 1989;Pollock et al, 1991;Taketomi et al, 1998;Ben-Eliyahu et al, 1999). The current study demonstrated that such adrenergic suppression is also modulated by the menstrual cycle, thus proposing this modulation as a mechanism contributing to the clinical phenomena.…”
Section: Discussionsupporting
confidence: 67%
“…We also suggest that adrenergic suppression of NK activity may be a mechanism contributing to the adverse effects of surgery. Suppression of NK activity after surgery is well documented clinically (Pollock et al, 1991;Brittenden et al, 1996), was attributed by animal studies to adrenergic mechanisms (Ben-Eliyahu, 1998a), and was suggested by human and animal studies to promote metastasis (Zoller et al, 1989;Pollock et al, 1991;Taketomi et al, 1998;Ben-Eliyahu et al, 1999). The current study demonstrated that such adrenergic suppression is also modulated by the menstrual cycle, thus proposing this modulation as a mechanism contributing to the clinical phenomena.…”
Section: Discussionsupporting
confidence: 67%
“…The immunosuppressive effects of surgical and anesthetic intervention include impaired T cell proliferation (39), decreased natural killer cell cytotoxicity (43), and altered phagocytic cell function (5,23). After surgery, the imbalance between pro-and anti-inflammatory cytokines released by monocytes and macrophages may promote dysfunction of innate cellular immunity and increased susceptibility to infection (35,59).…”
mentioning
confidence: 99%
“…Owing to its ability to seal vessels, it is possible that laser thermotherapy gives less intravascular tumour cell spread than surgical resection. Surgery has been shown to cause generalized immunosuppression, including depressed function of immune cells, such as lymphocytes, NK cells and non-parenchymal cells of the liver, which have the capacity to kill tumour cells (Pearson et al, 1986;Pollock et al, 1987Pollock et al, , 1992Colachio et al, 1994;Oka et al, 1994). Surgical resection also induces the production and release of growth factors, events that may stimulate cell division of tumours and facilitate recurrence and spread (Goustin et al, 1986;Fisher et al, 1989;Davies et al, 1994).…”
Section: Discussionmentioning
confidence: 99%